The lung in a cohort of rheumatoid arthritis patients—an overview of different types of involvement and treatment. (14th May 2019) - Duarte, Ana C; Porter, Joanna C; Leandro, Maria J
Abstract: Objectives: Lung involvement in RA has several manifestations and is a major cause of morbidity and mortality. The aim of this study was to characterize the different types of lung disease and response to treatment in a UK cohort of RA patients. Methods: RA patients who had undergone high resolution CT scans of the lung were identified and scans reviewed. Demographic data, RA features, complementary exams and treatments were recorded for those with radiological evidence of lung involvement. Descriptive analysis was performed, and Mann–Whitney U and χ 2 tests were used for comparison between different radiological subtypes. Results: Lung disease was reported in 87 (7.7%) of 1129 RA patients, usually (97.7%) post-dating articular symptoms. Most patients had positive RF (74/84; 88.1%) and ACPA (72/82; 87.7%). Interstitial lung disease (ILD) was the most common pattern, reported in 45 (51.7%) patients. Drug-induced lung disease was reported in 2 of 64 (3.1%) patients treated with MTX. Rituximab was used in 26 (57.8%) patients with ILD, with evidence of disease improvement or stabilization in patients with non-specific interstitial pneumonia and organizing pneumonia. During lung disease follow-up (6.7 ± 4.1 years), 22 (25.3%) patients were admitted to hospital with respiratory infections, with 14 (63.6%) of them having underlying bronchiectasis. Lung disease-related mortality was estimated at 8%. Conclusion: ILD was the most prevalent manifestation of lung involvement in RA and was associated with higher mortality. Immunosuppressive drugs used in RA were rarely associated with lung toxicity, and rituximab demonstrated promising results for the treatment of RA-ILD.